Monuments and monumentality: the cosmological model of the world of megaliths - Magdalena S. Midgley (Documenta Praehistorica, 2010)
Neolithic monuments are physical and conceptual expressions of ideas about the nature of the world inhabited by early north European farmers. This contribution explores the complex symbolism encoded in megalithic architecture, and the socio-ritual interactions within which megaliths offered venues for public gatherings in which individuals participated singly or as members of larger groups. By bringing communities together – be it in thanksgiving, worship or pilgrimage – megaliths bridged the gap between the immediate, quotidian and local realities of life and the anomalous entities of the multi-dimensional universe in which past, present and future were given tangible permanence.